Setting-up a sulh-based, community mediation-type of online dispute resolution (ODR) in Malaysia - Hassan, Raini; Ambaras Khan, Hanna; Al Shaikhli, Imad Fakhri Taha; Abdul Hak, Nora (2013)
Islam is a way of life that guides the Muslims from all perspectives, and as portion of Islam, it also promotes peace and conciliation in resolving disputes. The Al-Quran provides guidelines in dispute resolution through a third party called Sulh. Sulh refers to the process of mediation, arbitration and reconciliation that takes place when the parties involved agree on a process of resolving a dispute with a third party mediator, who eventually will ensure that both disputed parties will be satisfied by the outcomes. This work is focused on community mediation, which involved with the disputes between the community members. In Malaysia, Sulh were actually practiced by the Malays prior to the time of the Portuguese, the Dutch and the British. The session will be conducted by a third party who normally a respected and elder person in the society, whom also held the position as the headman (Penghulu or Ketua Kampung) or Imam (a religious leader). Nowadays, given the plural society of Malaysia, and the era of Internet, it is crucial for Sulh to be available online. With the use of ICT tools, Sulh can be promoted to society, and if it is a part of e-government efforts, then it will encourage the society to be involved with the government’s mission. The online Sulh will not merely act as an interface for those parties involved. The challenges of making the online system secured, the correct ways of ensuring the data accuracy, understanding on methods that will be used for data propagation (among others), are existed in the domain of Computer Science (CS). There are many possible CS approaches, but the work will focus on Computational Intelligence (CI) techniques, with special interest in connectionist models